2011
DOI: 10.5194/bg-8-2493-2011
|View full text |Cite
|
Sign up to set email alerts
|

Does terrestrial drought explain global CO<sub>2</sub> flux anomalies induced by El Niño?

Abstract: Abstract. The El Niño Southern Oscillation is the dominant year-to-year mode of global climate variability. El Niño effects on terrestrial carbon cycling are mediated by associated climate anomalies, primarily drought, influencing fire emissions and biotic net ecosystem exchange (NEE). Here we evaluate whether El Niño produces a consistent response from the global carbon cycle. We apply a novel bottomup approach to estimating global NEE anomalies based on FLUXNET data using land cover maps and weather reanalys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 67 publications
(94 reference statements)
0
23
0
Order By: Relevance
“…per year using a top-down approach, while Potter et al (2007) estimated uptake of 100 to 200 Pg CO 2 per year over the same period using a bottom-up method. Schwalm et al (2011) found conflicting estimates of global NEE anomalies estimated from upscaled FluxNet observations when compared against top-down inversion anomaly estimates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…per year using a top-down approach, while Potter et al (2007) estimated uptake of 100 to 200 Pg CO 2 per year over the same period using a bottom-up method. Schwalm et al (2011) found conflicting estimates of global NEE anomalies estimated from upscaled FluxNet observations when compared against top-down inversion anomaly estimates.…”
Section: Introductionmentioning
confidence: 99%
“…This method could in concept be applied to NEE as well, though the machine learning approach is purely empirical and does not attempt to incorporate any ecological understanding. Schwalm et al (2010) and Schwalm et al (2011) present methods to globally upscale FluxNet observations by plant functional type. These methods depend on the commonly employed assumption that plant functional types are good predictors of landcape NEP.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this, the El-Niño event of 2010 was associated with a higher CO 2 source in central Europe than the following La-Niña (negative ENSO) year (Bowman et al 2017), which instead led to very high NPP values across the continent (Bastos et al 2013). As a result, NEE over Europe shows a positive correlation with ENSO, albeit with important differences depending on region, El Niño event and method for calculating NEE (Schwalm et al 2011).…”
Section: Climate Indices and The Carbon Cyclementioning
confidence: 99%
“…The impact of annual to decadal oscillations in the climate system on terrestrial carbon uptake has been examined on local to global scales. For example, the effect of the phase of the El Niño-Southern Oscillation (ENSO) on global-scale photosynthesis and respiration, with ramifications for the global atmospheric CO 2 growth rate, has been particularly well studied (e.g., Gloor et al, 2018;Schwalm et al, 2011). These oscillations are themselves related to regional variability in multiple meteorological factors that may have additive or interactive effects on ecosystem carbon exchange (e.g., Jones et al, 2001;Knorr et al, 2007;Potter et al, 2003;Wharton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%